Employing a Continuous Measurement Process During Digital Tool Validation - Hughes, Nicolas; Rabieh, Khaled; Aydogan, Ahmet Furkan (Ieee, 2019)
As digital forensic laboratories face regulation and seek accreditation, examiners must fully validate the software and hardware used during forensic analysis. Tool validation is critical to any laboratory science as it provides analysts the empirical data necessary to draw conclusions about how laboratory instruments perform in realistic conditions. While digital forensic tools perform many common tasks, few robust validation methods exist for evaluating how tools perform those tasks. Developing validation methods that are feasible and robust is critical to both establishing digital forensics as a reliable discipline and accreditation requirements. This paper proposes a more comprehensive model of tool validation by taking continuous measurements a tool validation process. This continuous measurement process could later be repeated over all the scenarios that lab would expect to encounter in day-to-day operations. We attempt to determine whether or not a continuous model provides the sort of data necessary for empirical analysis of a digital forensic tool. Moreover, we propose a fully automated model for tool validation, permitting researchers to concentrate on validation study design rather than performing time-consuming, error-prone tasks on the test platform.
International Symposium on Networks, Computers and Communications (ISNCC) -- JUN 18-20, 2019 -- Istanbul, TURKEY
Keywords: Digital forensics; validation studies; continuous measurement process; forensic metrology; empirical data